Economics Students' Attitudes Towards Mathematics - Joshi, Bishnu M. (CMC Journal, 2026)
The quantitative nature of economics needs a strong understanding of mathematics. Mathematics is essential for analyzing markets, interpreting data, forecasting trends, testing economic theories, and informing decisions in financial investments and business strategies. This study synthesizes the attitudes of economics students towards mathematics, a critical factor influencing academic achievement and career success. Using a theoretical framework i.e. Katz’s functional theory of attitude formation and the ABC model, this study defines student attitudes as a complex interplay of emotional responses, behaviors, and beliefs. The review highlights the foundational role of mathematics in economics, from basic algebra to advanced econometrics, and explores the key factors shaping students' attitudes. It identifies perceived relevance, mathematics anxiety, self-efficacy, and pedagogical methods as primary influencers. This study discusses the significant impact of these attitudes on academic performance and future career trajectories, noting that negative pedagogical interventions, including emphasizing real-world applications, implementing active learning strategies, and explicitly addressing mathematics anxiety, can foster positive attitudes and better prepare students for the demands of a modern, data-driven economy.